2013
DOI: 10.11604/pamj.2013.14.5.1148
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with severe occupational injuries at mining company in Zimbabwe, 2010: a cross-sectional study

Abstract: IntroductionInjury rate among mining workers in Zimbabwe was 789/1000 workers in 2008. The proportion of severe occupational injuries increased from 18% in 2008 to 37% in 2009. We investigated factors associated with severe injuries at the mine.MethodsAn unmatched 1:1 case-control study was carried out at the mine, a case was any worker who suffered severe occupational injury at the mine and was treated at the mine or district hospital from January 2008 to April 2010, a control was any worker who did not suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 7 publications
(7 reference statements)
5
33
1
Order By: Relevance
“…This finding contradicted the qualitative study by Yu et al ,32 which state that use of PPE will reduce risk of injury among informal e-waste workers in Ghana. It also contradicted a study among miners where use of PPE was associated with risk of injury 33. In our study, use of PPE was associated with a higher reported occurrence of injuries.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding contradicted the qualitative study by Yu et al ,32 which state that use of PPE will reduce risk of injury among informal e-waste workers in Ghana. It also contradicted a study among miners where use of PPE was associated with risk of injury 33. In our study, use of PPE was associated with a higher reported occurrence of injuries.…”
Section: Discussioncontrasting
confidence: 99%
“…However, during this time when the road conditions were empty, these signs are not obeyed. Whereas other heavy equipments may appear suddenly (Chimamise et al, 2013). This is in line with Kurniawati research (2014), carrying out the work according to SOP will reduce the risk of occupational accidents.…”
Section: Discussionsupporting
confidence: 75%
“…This study represents the first attempt to report on the prevalence of WMSDs among nurses in the country. This novelty renders comparison with local studies difficult as they targeted different occupational groups [ 19 , 29 , 30 ]. Nevertheless, innumerable studies have been conducted on WMSDs among nurses worldwide [ 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%